Interest Limitation Rules and Corporate Tax Avoidance: A Cross-Country Analysis - Dewantara, Andreas Rossi (Directorate General of Taxes, 2025)
This study examines the impact of interest limitation rules on corporate tax avoidance and financing decisions. Interest from debts is tax-deductible, making debt financing attractive for firms, yet it also poses a risk for tax avoidance, leading to global tax revenue losses estimated between 125 to 280 billion annually. Tax authorities have implemented rules limiting interest deductibility, such as the debt-to-equity ratio (